An input-output analysis of the total factor productivity growth of the Malaysian manufacturing sector, 1983-2005 - Noorasiah Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines total factor productivity (TFP) growth of the Malaysian manufacturing sector from 1983 to 2005. Unlike previous studies that use one source of data.this research use two sources of data-Malaysian Input-Output tables and Malaysian industrial manufacturing Survey. The motivation for this study brought about due to the need to present a different method for estimating TFP growth by analysing TFP using the input-output methodology.The results from this study are compared with the results from other studies that use a different method to estimate TFP growth and the findings indicate that the TFP growth is relatively low.In addition, the major source of change in TFP of the manufacturing sector is contributed by intermediate inputs, while the contribution of labour and capital is substantially low.